Hotel Tax Optimization Strategy Through Regulatory and Root Cause Approach - Suparmono, Suparmono (Telaah Bisnis, 2024)
This study aims to analyze the root causes of suboptimal regional tax revenues, especially from hotel taxes. The research location is in Klaten Regency, Central Java Province. The analysis tool used is root cause analysis (RCA). Data collection was carried out using interview techniques, observation, regulatory analysis, and other possible primary data collection techniques. Primary data was obtained from interviews and FGDs with hotel managers and other stakeholders, while data collection techniques were carried out using stratified cluster sampling for each class of star and non-star hotels. From the results of the analysis, it was concluded that there were four root causes. First, the transition period for the implementation of Law Number 1 of 2021 concerning financial relations between the central and regional governments (HKPD) which makes it difficult for regions to collect. Second, the implementation of an information technology-based tax collection system has not been carried out. Third, the location of Klaten Regency is flanked by the cities of Solo and Yogyakarta. Fourth, there are no objects that are the main attractions for tourists to visit Klaten Regency which require a visit time of more than one day. Improvement and updating of the taxpayer database and potential revenue from each hotel, implementation of the tapping box system through cooperation between local governments and banks, digitalization of the hotel tax recording system, and cooperation in pricing strategies between hotels are the four main strategies for increasing hotel taxes in Klaten Regency.